- 19
- 0
I was looking up stuff for relativistic two-body decay, and I came across this pdf: https://indico.cern.ch/event/391122/contributions/928962/attachments/782786/1073126/twoBodyDecay.pdf
which says that because ##p_2^2=P^2−2P\cdot p_1+p_1^2## we apparently have ##m_2^2=M^2−2ME_1+m_1^2##. But this doesn't seem correct, given that ##p_1=(E_1/c,\vec{p_1})##.
Is it correct? If so, how do we get there?
which says that because ##p_2^2=P^2−2P\cdot p_1+p_1^2## we apparently have ##m_2^2=M^2−2ME_1+m_1^2##. But this doesn't seem correct, given that ##p_1=(E_1/c,\vec{p_1})##.
Is it correct? If so, how do we get there?